New perspectives in Audiovisual Translation: Towards Future Research Trends (2022)
The aim of this book is to contribute to the dissemination of current research carried out by young scholars who are starting to build promising careers in the field of audiovisual translation. Although it is by no means an exhaustive collection of state-of-the-art approaches to AVT, this publication offers a carefully chosen list of research perspectives that are worth exploring in the current technologised landscape that this area of translation has become. Therefore, it represents a select yet judicious group of studies, with the added strength that the contributions presented here are not limited to academic circles, but rather offer different points of view from various angles, given the diverse profiles that characterizes the authors. Thus, each chapter deals with the subject of AVT from an academic, educational or professional perspective. As diverse as their approaches are, all the young authors who have collaborated to create this volume offer enriching perspectives that reflect the potential that AVT still has today and the prospective studies that are worth undertaking to continue enriching the field of AVT.El objetivo de este libro es contribuir a la difusión de las investigaciones actuales llevadas a cabo por jóvenes que están comenzando a construir carreras prometedoras en el campo de la traducción audiovisual (TAV). Aunque no se trata de una recopilación exhaustiva de los enfoques más avanzados en este sector, se ofrece un conjunto cuidadosamente seleccionado de perspectivas de investigación que merece la pena explorar en el actual panorama tecnificado en el que se ha convertido este ámbito de la traducción, estudios que tienen el valor añadido de que no provienen solo de círculos académicos, sino que, dados los diversos perfiles que caracterizan a autoras y autores, representan diferentes puntos de vista: académico, educativo y profesional. Por muy diversos que sean los enfoques, se ofrecen visiones enriquecedoras que reflejan el potencial que la TAV tiene todavía hoy y los estudios prospectivos que merece la pena realizar para seguir enriqueciendo este campo.
Keywords: traducción; localización; traducción audiovisual; doblaje; subtitulación; subtítulos; accesibilidad; videojuegos; cómics; audiodescripción; subtitulación para sordos